Evaluasi Struktur Gedung Hotel Swiss-Belhotel Darmo Surabaya Menggunakan Analisis Pushover Berdasarkan SNI 1726-2019 - Heri Istiono; Yanisfa Septiarsilia; Dita Kamarul Fitriyah; Indra Komara; Felicia Tria Nuciferani (Jurnal Teknologi dan Manajemen, 2023)
Earthquake-resistant buildings are mandatory in Indonesia because of its high level of earthquake vulnerability. For this reason, the Swiss-Belhotel Darmo, Surabaya as a reference for evaluation, the researcher employed SNI 1726-2019 regarding the procedures to plan earthquake resistance for building and non-building structures. This regulation is widely used currently for planning the structure of buildings to substitute SNI 1726-2012 buildings. Pushover analysis is implemented to evaluate the structure to get the curves of pushover capacity, performance level, and displacement target based on FEMA 356 as well as the ductility occurring in the building structure. The evaluation results demonstrated that the mass participation in the 7th capital, the base shears of É²x and É²y were greater than 1, and thus, they have met the requirements. The Story drift did not meet the requirements because its value exceeded the permit limit. Shearwall's contribution fulfilled the requirement of more than 25%. Meanwhile, the control of time history obtained the basic shear results satisfying the requirements for all seismic forces, but the story drift value dissatisfied the requirements because it exceeded the permissible limit for Y seismic force and Y direction. The results of the pushover analysis yielded a drift ratio value of 0.01. Hence, according to FEMA 356, the level of performance was immediate occupancy.